Chemical Weapons Violations in Syria's Civil War: an International Law Perspective - Yordan Gunawan; Mhd. Ervizal Rizqy Pane; Muhammad Reza Athallah (Amnesti Jurnal Hukum, 2023)
The use of chemical weapons in the Syrian civil war is a grave violation of international law, as it violates the prohibition on using chemical weapons under customary international law. The war has erupted since Syrian President Bashar Al-Assad responded violently to the peaceful opposition toward the regime. The Organization for the Prohibition of Chemical Weapons (OPCW) has confirmed two occasions of using chemical weapons in Syria in 2015 and 2016. However, until recently, there were no necessary measures to protect civilians in Syria from using chemical weapons and prevent any future use of Syria's stockpile of chemical weapons. The study aims to analyze the use of chemical weapons in the Syrian civil war, the violation of the CWC in the Syrian civil war, and the legal protection of Syrian civilians. The study used a normative legal research methodology. The data sources in the study were secondary data obtained from the statutory, analytical, legal, conceptual, and fact approaches. The study's result showed that the Syrian government violated the Chemical Weapons Convention of 1993 (CWC) and should respond with the action, categorized as an infringement of the international legal norm.